INTERNATIONAL BLOWN GLASS SYMPOSIUMS IN LVIV: INFLUENCE LEVEL IN UKRAINIAN DECORATIVE ART ON THE EDGE OF CENTURIES - Roksolana, Patyk; Mykhailo, Bokotei; Oleksandr, Honcharuk; Volodymyr, Honcharuk; Skrynnyk–Mys’ka, Daryna (International Journal of Psychosocial Rehabilitation, 2020)
A strong creative impulse, a scope of glass manufacture in the second half of the 20th century led to the emergence of a studio glass movement that has become a phenomenon of the 20th-century art. This study focuses precisely on the issues concerned with the processes of developing of international studio glass movement in Ukraine and particular influence for it by the activity of International Blown Glass Symposiums in Lviv, that for over thirty years links activities of leading artists from more than 30 countries. The article aims to analyze the activity of the International Blown Glass Symposiums in Lviv and estimate it’s influence on the Ukrainian glass art, developing in the framework of global International studio glass movement. Through a comparison method of the creative activity of individual artisans, participating in the glass symposiums, a general picture of world glass art activity has been acquired, which allows an estimate of the influence on contemporary Ukrainian glass art.